ESG and Industrial Perfomance - Atika Rahmi (CONTABILITA : Journal of Accounting and Finance, 2025)
This study aims to examine the effect of Environmental, Social, and Governance (ESG) disclosure on firm performance as a reflection of sustainable corporate practices. ESG disclosure represents a company’s accountability toward environmental protection, social responsibility, and good governance implementation, which are essential pillars of green accounting. Using firm performance as the primary indicator of corporate success, this research investigates how ESG initiatives and leadership duration interact to drive organizational outcomes. The results reveal that ESG disclosure has a negative and significant impact on firm performance, indicating that higher ESG engagement may initially increase costs or reduce short-term profitability. This implies that experienced CEOs can enhance the value of ESG initiatives, mitigating potential inefficiencies and reinforcing sustainable performance over time. The findings contribute to the development of green accounting literature by emphasizing the importance of leadership stability and transparent ESG reporting as integral components of corporate sustainability